2012
DOI: 10.5433/1679-0359.2012v33n6p2411
|View full text |Cite
|
Sign up to set email alerts
|

Curva de desidratação e composição químico-bromatológica do feno de grama-estrela (Cynodon nlemfuensis Vanderyst) em função do teor de umidade no enfardamento

Abstract: Curva de desidratação e composição químico-bromatológica do feno de grama-estrela (Cynodon nlemfuensisVanderyst ResumoObjetivou-se determinar a curva de desidratação e o efeito do teor de umidade no enfardamento sobre a composição químico-bromatológica do feno de grama-estrela (Cynodon nlemfuensis Vanderyst). Foram realizadas amostragens do momento do corte até o enfardamento, a fim de determinar a curva de desidratação da planta inteira e das frações folha e colmo, com secagem em estufa de ventilação forçada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…These rates were higher than those obtained by Calixto et al (2012) in star grass (Cynodon nlemfuensis), in which the average rate was 0.9% of DM per hour. These values were higher than those obtained by Silva et al (2011), corresponding to 1.44-1.89% of DM per hour.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…These rates were higher than those obtained by Calixto et al (2012) in star grass (Cynodon nlemfuensis), in which the average rate was 0.9% of DM per hour. These values were higher than those obtained by Silva et al (2011), corresponding to 1.44-1.89% of DM per hour.…”
Section: Resultscontrasting
confidence: 70%
“…*significant at p<0.05 for the linear effect; ns, not significant at p<0.05 for the linear effect. Calixto et al (2012) found that hay-making consisted of decreasing forage moisture to values below 20% and obtaining a DM of 80%, allowing safe storage of hay and low rates of loss of CP. Therefore, the Massai cultivar presented the highest drying efficiency, reaching a safe storage moisture content after 3 h and 6 min of sun exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analyzes were performed using Genes software (Cruz, 2013). A correlation matrix between the characteristics was estimated, which was tested for multicollinearity by the matrix condition number (NC) proposed by Montgomery et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…The phenological process is generally carried out in grasses that present high mass production and high water loss capacity, but in forage legumes it is a little disseminated practice in national livestock (CALIXTO Jr. et al, 2012, SILVA et al al., 2015. The adoption of legumes for this process is restricted to the massive use of alfalfa (Medicago sativa), which originates from the temperate climate, since this climatic factor makes it difficult to cultivate this species in the most of Brazilian territory (SILVA et al, 1995;NERES et al, 2010).…”
Section: Introductionmentioning
confidence: 99%